Sustainable development of rainfed agriculture in India - Kerr, John M. (International Food Policy Research Institute, 1996)
India's agricultural growth has been sufficient to move the country from severe food crises of the 1960s to aggregate food surpluses today. Most of the increase in agricultural output over the years has taken place under irrigated conditions. The opportunities for continued expansion of irrigated area are limited, however, so Indian planners increasingly are looking to rainfed, or unirrigated agriculture to help meet the rising demand for food projected over the next several decades. Given that rainfed agriculture should receive greater emphasis in public investments, a key issue is how much investment should be allocated among different types of rainfed agriculture. This paper addresses a wide variety of issues related to rainfed agricultural development in India. It examines the historical record of agricultural productivity growth in different parts of the country under irrigated and rainfed conditions, and it reviews the evidence regarding agricultural technology development and adoption, natural resource management, poverty alleviation, risk management, and policy and institutional reform. It presents background information on all of these topics, offering some preliminary conclusions and recommending areas where further research is needed. The analysis of agricultural productivity growth is based on district level data covering the Indo-Gangetic plains and peninsular India from 1956 to 1990.